KOMUNIKASI NONVERBAL DALAM GERAK TARI HIP HOP - Zaus, Anggi Agni; Bungin, Burhan; Sumarah, Noorshanti (representamen, 2015)
Hip-hop dance is a dance that is part of hip hop culture, developed by African American society thathas its own characteristics. This dance is growing and more popular among young people. This studyused descriptive qualitative method. With semiotic approach and to answer the problem what is themeaning of non-verbal communication in hip hop dance movement and how the message is delivered tothe audience from hip hop dance itself. The result of research shows that hip hop dance has non verbalcommunication meaning hip hop dance, hip hop dance, hip hop dance, and hip hop dance. hip hop isshown as an entertainment performing arts for the audience for all ages not just young people. Dance isdisplayed with the feel of young people in the form of happiness and freedom of expression. Non-verbalcommunication in this dance whose message content is to convey their existence through a hip hop danceconceptKeywords: hip hop, culture, non verbal, communication